Comparison of Early Treatment Outcomes for Large Macular Hole Using Various Surgical Techniques - D. V. Petrachkov; L. Alkharki; A. G. Matyushchenko; V. M. Filippov; F. K. Dudieva (Oftalʹmologiâ, 2021)
Macular hole (MH) is one of the most common pathologies of the macular area of the retina which leads to a significant decrease in visual acuity. The article presents early comparative morphofunctional results of surgical treatment of 60 patients (22 men and 38 women) with MH of the III–IV stages according to Gass and the minimum diameter (MinD) MH 404–696 microns. All patients included in the study had pseudophakia and have not previously undergone endovitreal interventions. Patients with MH with a diameter of 404–696 μm were randomized and divided into 3 equal groups: after three-port 25G pars plana posterior vitrectomy the patients of the first group underwent peeling of the inner limited membrane (ILM) with the convergence of the edges of MH and vitreous cavity tamponade with 16 % gas-air mixture of perfluoropropane (C2F6). In the area of the macular defect, patients of the second group underwent application of autologous conditioned plasma (ACP) in the PFСs environment and the convergence of the edges of MH. In patients of the third group, MH was closed using the technique of an inverted ILM flap. In patients of groups 2 and 3 the operation was completed by tamponade of the vitreous cavity with sterile air. Standard and special research methods, such as optical coherence tomography of the macular zone, were performed before surgery, 5 days and 1 month after surgery in all patients from groups 2 and 3. Patients from group 1 were examined before surgery and 1 month after surgical treatment, due to the long-lasting gas-air mixture in the vitreous cavity. Restoration of the correct structure of the fovea with the formation of U- and V-shaped profile during OCT after 1 month was noted in all cases. The data obtained demonstrate the peculiarities of using the inverted ILM flap and ACP methods in comparison with the traditional method of MH closure with a gas-air mixture.